Pembelajaran Materi Jasa Lingkungan - Sri Murni Soenarno (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2014)
Indonesia has an abundance nature resource. Unwisely nature resources utilization through over-exploitation results in nature deterioration in Indonesia. Over-exploitation affects the environmental service supplies and endangers human being in the future. Environmental services utilization is an effort to utilize the potential services of ecosystem functions without destroying and reducing the main functions. For the sake of guarantee sustainable life on the earth, it is required student understanding of environmental services; therefore it needed teachers who understand of environmental services. This article is based on the research about teacher understanding toward environmental services and perceptions about the importance of teaching environmental services material to junior high school student. Majority opinion of the teachers is important to educate environmental services for the future of nation.